Radiolysis of Reactive Azo Dyes in Aqueous Solution - Agustin N.M. Bagyo; Winarti Andayani; Hendig Winarno; Ermin Katrin; Yanti S. Soebianto (PPIKSN-BATAN, 2004)
The effects of radiation on aerated reactive dye solutions i.e Cibacron Violet, Cibacron Orange and Cibacron Yellow solutions have been studied. Parameters analysis were the change of pH after radiation, the change of absorption, degradation products and effects of pH on the radiolysis. The uv-vis absorption of solutions were observed before and after irradiation. pH variation was done from pHs 3, 5, 7, 9 and 12. Irradiation was done at doses of 0, 2, 4, 6, 8 and 10 kGy with dose rate of 5 kGy/h and was determined by a Fricke dosimeter. HPLC with UV detector was used to analyze the degradation products. Oxalic acid was the main degradation product and small amount of succinic acid was also detected.